Semiotische Effizienz interfachlicher Sprache-Bild-Textsorten : Schreibprozesse bei Pflichtenheften technischer Ausschreibungen - Holste, Alexander (Berlin Frank & Timme, 2019)
Communicative efficiency can be measured with conventions. Besides linguistic means, pictures and diagrams are also an expression of such conventions. In the practice of technical editing, this refers to multimodal text types with technical language elements, photographs, technical drawings, various types of diagrams, etc. Alexander Holste uses the example of the text type specification sheet to show how an inter-disciplinary team of engineers, lawyers, business economists, etc. negotiates these conventions. The different, technically justified ideas of the text type conventions, especially with regard to the choice of multimodal means of expression, become clearly apparent. Requirement specifications are created in the context of the tendering of public contracts by public authorities. Since such contracts represent an important field of work for the companies involved, the efficient design of the specifications is highly relevant from a business management point of view. Alexander Holste, Dr. phil., studied German as well as business administration in Essen and Turin and headed the technical editorial department of a public transport company before he started teaching professional and scientific writing at the University of Duisburg-Essen in 2009, especially for engineering scientists. His research interests lie in the fields of semiotics, text linguistics, technical communication and writing didactics.
German
Keywords: Semantics, discourse analysis, etc; Interdisciplinary studies; communication; semiotics; efficiency; communicative efficiency; semiotic efficiency; Language-image-text types; Language-image-text varieties; textual design; technical editing; technical writing; technical tendering, technical tenders; text type requirement specification; text type conventions